Protocol for the establishment of murine orthotopic lung tumors and the assessment of contralateral pulmonal metastasis by flow cytometry - Gregor Zaun; Siyang Liu; Maximilian Webendörfer; Abubakar Wani; Diego Rodriguez; Douglas R. Green; Halime Kalkavan (STAR Protocols)
Summary: Murine orthotopic tumor models can accurately resemble cancer biology characteristics including metastasis, drug sensitivity, and remodeling of the tumor microenvironment. Here, we present a protocol for establishing murine orthotopic lung tumors and assessing contralateral pulmonary metastasis by flow cytometry. We describe steps for marking tumor cells with label retention dyes, preparing cell mixtures in Matrigel, and performing intrapulmonary injection. We then detail procedures for ex vivo processing of lungs followed by fluorescence-activated cell sorting (FACS) data analysis and quantification of metastatic capacity.For complete details on the use and execution of this protocol, please refer to Kalkavan et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.